2019
DOI: 10.1038/s41598-019-56401-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel Arabidopsis pathosystem reveals cooperation of multiple hormonal response-pathways in host resistance against the global crop destroyer Macrophomina phaseolina

Abstract: Dubbed as a “global destroyer of crops”, the soil-borne fungus Macrophomina phaseolina (Mp) infects more than 500 plant species including many economically important cash crops. Host defenses against infection by this pathogen are poorly understood. We established interactions between Mp and Arabidopsis thaliana (Arabidopsis) as a model system to quantitatively assess host factors affecting the outcome of Mp infections. Using agar plate-based infection assays with different Arabidopsis genotypes, we found sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 101 publications
(120 reference statements)
1
13
0
Order By: Relevance
“…Our report was corroborated by another group with transcriptome analysis using the same pathosystem (Yan et al, 2021). Later, in a similar report by Schroeder et al, 2019, with Arabidopsis as host, the pathogen evoked mainly SA-mediated defense response in early phases which shifted to JA/ET alone in the later phases. Our finding that CHS1 and CHS2 has been increased in SA-primed plants in response to infection is similar to the observations made by Campos et al, 2003 on the hemibiotrophic pathogen Colletotrichum sp.…”
Section: Discussionsupporting
confidence: 86%
“…Our report was corroborated by another group with transcriptome analysis using the same pathosystem (Yan et al, 2021). Later, in a similar report by Schroeder et al, 2019, with Arabidopsis as host, the pathogen evoked mainly SA-mediated defense response in early phases which shifted to JA/ET alone in the later phases. Our finding that CHS1 and CHS2 has been increased in SA-primed plants in response to infection is similar to the observations made by Campos et al, 2003 on the hemibiotrophic pathogen Colletotrichum sp.…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, ET or JA mutants showed an enhanced susceptibility to M. phaseolina. These observations suggested that ET and JA signaling pathways are important for protection against M. phaseolina in Arabidopsis (Schroeder et al, 2019).…”
Section: Host Plant -M Phaseolina Interactionmentioning
confidence: 86%
“…The fungus Macrophomina phaseolina is a noxious pathogen that infects more than 500 host plant species belonging to about 100 families globally (Schroeder et al 2019). The pathogen has a wide geographical distribution, and is commonly found in Europe, Africa, Asia, South and North America (Zimudzi et al 2017).…”
Section: Introductionmentioning
confidence: 99%